2022
DOI: 10.1111/dgd.12818
|View full text |Cite
|
Sign up to set email alerts
|

A novel agonist for the HGF receptor MET promotes differentiation of human pluripotent stem cells into hepatocyte‐like cells

Abstract: Hepatocyte growth factor (HGF) is the natural ligand of the MET receptor tyrosine kinase. This ligand-receptor couple is essential for the maturation process of hepatocytes. Previously, the rational design of a synthetic protein based on the assembly of two K1 domains from HGF led to the production of a potent and stable MET receptor agonist. In this study, we compared the effects of K1K1 with HGF during the differentiation of hepatocyte progenitors derived from human induced pluripotent stem cells (hiPSCs). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Plasma membrane depolarization by the inhibition of K Ca 1.1 may also be involved in the inactivation of the Akt signaling pathway through a decrease in the intracellular concentration of Ca 2+ . In addition to the Akt signaling pathway, the JNK and ERK signaling pathways are also important for the acquisition of DOX resistance and the transcriptional regulation of CYP3A4 in cancerous and non-cancerous cells [17,[27][28][29]. In the previous study, we showed the involvement of K Ca 3.1 in the regulation of JNK and ERK signaling pathways in macrophages [30].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Plasma membrane depolarization by the inhibition of K Ca 1.1 may also be involved in the inactivation of the Akt signaling pathway through a decrease in the intracellular concentration of Ca 2+ . In addition to the Akt signaling pathway, the JNK and ERK signaling pathways are also important for the acquisition of DOX resistance and the transcriptional regulation of CYP3A4 in cancerous and non-cancerous cells [17,[27][28][29]. In the previous study, we showed the involvement of K Ca 3.1 in the regulation of JNK and ERK signaling pathways in macrophages [30].…”
Section: Discussionmentioning
confidence: 95%
“…No significant changes in the relative expression level of CEBPB transcripts were found by a single treatment with SC79 or NK252 in LNCaP, MG-63, and SW-1353 spheroid models (n = 4, p > 0.05) (Figures 10 and 11). In addition to the Akt-Nrf2 signaling pathway, the JNK/Nrf2 and ERK/Nrf2 pathways contribute to the acquisition of DOX resistance [17,27] and the regulation of CYP3A4 expression [28,29]. A recent study showed that the Ca 2+ -activated K + channel, K Ca 3.1, potentially regulates the JNK and ERK signaling pathways [30].…”
Section: Involvement Of the Akt-nrf2 Signaling Pathway In Cebpb Trans...mentioning
confidence: 99%